Effects of selective RNA processing and stabilization enzymes on carbon sequestration by photosynthesis of Synechococcus sp. PCC7002 - Chen, Jinyu; Liu, Daixi; Wang, Yafei; Wang, Shaoyu; Huang, Ranran (Frontiers in Marine Science, 2023)
Synechococcus is one of the most abundant prokaryotic photosynthetic organisms on Earth and plays a key role in oceanic carbon fixation and transformation. To improve the photosynthetic efficiency of synechococcus, a post-transcriptional regulatory mechanism - Selective RNA Processing and Stabilization (SRPS) was considered. We inactivated the SRPS-enzymes, executor of the SRPS mechanism, to explore their regulation rule of photosynthetic carbon fixation efficiency in Synechococcus. The results showed that the inactivation of SRPS-enzymes mainly affected the growth rate or growth phase. It significantly alters the photosynthetic oxygen evolution rate, pigment content, chlorophyll fluorescence, carbon and nitrogen content, as well as the composition and biological activity of the dissolved organic matter derived from Synechococcus (SOM). Inactivating SRPS-enzymes results in an increase in the expression level of most subunits of the Cytochrome b6-f complex, while the expression levels of most subunits of PSI, PSII, RuBisCO, and NDH decrease. All SRPS-enzymes are involved in the expression regulation of basilic protein complexes in photosynthesis, such as PSI, PSII, Cytochrome b6-f complex, ATP synthase, and RuBisCO. Our results indicate that the inactivation of SRPS-enzymes have a significant influence on carbon sequestration by photosynthesis of Synechococcus sp. PCC7002.